Efficient Map/Reduce secure data using Multiagent System - Kousar, H; Babu, BRP (International Journal of Computer Sciences and Engineering, 2025)
Today is an era of digital world where technology and information play a very important role in our lives. Huge amount of data is generated, more than in terms of zetabytes and this data is been transmitted over an internet. Data is from Internet search, mobile devices, Internet of Things which include variety of objects like tablet, sensors, smart phones, digital cameras, tablets, etc., business transactions, Government organization, next generation radio astronomy telescopes, traffic data etc. This result in the raise of big data application. Current technologies i.e. Hadoop is unable to process data and secure the data within a given elapsed time. In this paper we proposed Multiagent Map Reduce Secure Model (MMRSM) using cloud. MMRSM supports both batch processing of data and Streaming of data. The proposed system supports both data security and efficient resource management of processing streaming data with minimum cost and time.